Exploring Women's Support Needs After Breast Reconstruction Surgery: A Qualitative Study. Issue 2 (March 2019) - Carr, Tracey L.; Groot, Gary; Cochran, David; Vancoughnett, Mikaela; Holtslander, Lorraine
Abstract : Background: The procedures for breast reconstruction (BR) after mastectomy frequently initiate a difficult recovery period. A better understanding of women's support needs after surgery would improve patient care. Objective: The aim of this study was to identify patients' support needs after BR. Methods: In a retrospective study design, 21 participants described their support experiences after BR, including their sources of support and the impact of support on their recovery in a semistructured interview. Transcriptions of the interviews were analyzed using thematic analysis. Results: Four support needs were identified and were composed of elements of instrumental, emotional, and informational support. These needs were addressed to varying degrees by healthcare providers, family members, and other women who had BR experience. Conclusion: Women's experience of BR and their ability to cope are markedly better when their support needs are effectively addressed. Greater attention to their needs for support has the potential to improve patient care. Implications for Practice: Nurses play a pivotal role in providing information to women who are recovering from BR. Improved access to communication channels between nurses and patients would likely improve patients' support experiences. In addition, nurses can assess the women's specific support needs and partner with families to help them understand how best to support women during recovery.